1998
DOI: 10.1038/sj.cdd.4400406
|View full text |Cite
|
Sign up to set email alerts
|

The CD95/CD95 ligand system is not the major effector in anticancer drug-mediated apoptosis

Abstract: Many anticancer drugs are able to induce apoptosis in tumor cells but the mechanisms underlying this phenomenon are poorly understood. Some authors reported that the p53 tumor suppressor gene may be responsible for drug-induced apoptosis; however, chemotherapy-induced apoptosis can also be observed in p53 negative cells. Recently, doxorubicin (DXR) was reported to induce CD95L expression to mediate apoptosis through the CD95/CD95L system. Thus, an impairment of such a system may be involved in drug resistance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…In agreement with previous reports in different experimental models 19,46 our results indicate that ETO-or CPT-induced apoptosis of activated PBL may be in part independent of caspases activation. It was already reported that some death inducers, such anti-CD2 monoclonal antibodies, staurosporine as well as the pro-apoptotic protein Bax 47,48 which induce caspase activation are however not blocked by the broad spectrum inhibitor zVAD.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In agreement with previous reports in different experimental models 19,46 our results indicate that ETO-or CPT-induced apoptosis of activated PBL may be in part independent of caspases activation. It was already reported that some death inducers, such anti-CD2 monoclonal antibodies, staurosporine as well as the pro-apoptotic protein Bax 47,48 which induce caspase activation are however not blocked by the broad spectrum inhibitor zVAD.…”
Section: Discussionsupporting
confidence: 82%
“…10,15 More recently chemotherapeutic agents such as doxorubicin, ETO and teniposide were shown to induce a rapid up-regulation of CD95-L via the activation of the SAPK/JNK pathway. 12,16 However these results remain controversial 17 and the observation that some Fas-resistant cell lines undergo apoptosis after treatment with ETO and doxorubicin 11,18,19 suggested that in addition to the CD95/CD95-L pathway other mechanisms may be involved in drug-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…[54][55][56][57] However, induction of CD95-L following drug treatment was also found in these studies. 55,56 The discrepancy between different results may reflect differences in cell lines used, kinetics, cell culture conditions, drug concentrations and concentrations or effectiveness of blocking antibodies. Drug-induced apoptosis may also involve cell type-specific activation of parallel pathways such as death receptor pathways and mitochondrial pathways.…”
Section: Drug-induced Cd95-independent Pathwaysmentioning
confidence: 80%
“…Initial studies revealed that cytotoxic drugs can activate death receptor/caspase-8 signalling pathways and this mechanism may be an essential factor in the early phase of drug-induced cell death depending on the cell type used (Friesen et al, 1996;Fulda et al, 1997Fulda et al, , 1998aFulda et al, , b, 2000Micheau et al, 1997). However, not all cell types require death receptorligand interaction for drugs to be effective (Gamen et al, 1997;Eischen et al, 1997;Villunger et al, 1997;Tolomeo et al, 1998;RuizRuiz and Lopez-Rivas, 1999). Recent studies have indicated that caspase-8 can be activated independently of death receptor ligation (Milner et al, 2002).…”
mentioning
confidence: 99%